South Korean Development Cooperation in Africa: The Legacy of a Developmental State. Issue 3 (December 2016) - Kalinowski, Thomas; Park, Min Joung
This paper investigates how the legacy of the South Korean developmental state influences the way the country conducts its development cooperation (DC) policies. We argue that institutions of the developmental state remain instrumental in structuring South Korea's cooperation with the developing world. Two country case studies of South Korean DC and investment projects in Mozambique and Rwanda show that state initiative and a strong state–business partnership are defining elements of South Korean DC. At the same time, both cases show substantial differences when it comes to type of project, type of state–business partnership in the South Korean approach, degree of project ownership by the recipient country, and quality of governance in the recipient countries.